Finite element heat transfer analysis of martensitic transformation latent heat storage Nickel Titanium shape memory alloy/aluminum composite - Hiroyuki KATO; Yuta NAITO (Mechanical Engineering Journal)
A heat-storage device using the latent heat of the martensitic transformation in Nickel Titanium (NiTi) shape memory alloy (SMA) is proposed. The principle of heat-storage is such that, when a piece of NiTi SMA in the state of fully transformed martensite is in contact with a heat source, the piece would absorb a part of heat as the latent heat associated with the phase change from the martensite to austenite. Since the feasibility study of the device has not yet been given, this article presents the computer simulation of the device by considering the composite of NiTi SMA rods embedded in the block of aluminum. The composite is designed to cool down the temperature of a heat source by being in contact with the aluminum block including SMA rods. The absorption of latent heat is expressed in the equation of the continuous change in the enthalpy, which makes it possible to perform the heat transfer analysis of finite element method (FEM). The enthalpy function is derived from the experimental result of differential scanning calorimeter. The result of FEM exhibits the performance of the proposed heat storage composite quantitatively.